2018
DOI: 10.1093/jnen/nly032
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Drive Inflammation and Target Gray Matter and the Retina in Autoimmune-Mediated Encephalomyelitis

Abstract: Despite growing evidence for platelets as active players in infection and immunity, it remains unresolved whether platelets contribute to, or are key elements in the development of neuroinflammation. Using the experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis, we identified platelet accumulation in the circulation by 7-day postinduction (dpi), ahead of clinical onset which occurs at 13-14 dpi. By inducing platelet depletion between 7 and 16 dpi, we demonstrate an association between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…To determine whether a direct relationship exists between platelet and MOG 35–55 -CD4 + accumulations, ICS was repeated in the presence of platelet depletion, which was induced from 7 dpi using an antibody against CD42b (or GP1bα). In our hands [25], this approach results in reduction in platelet numbers in all control and experimental groups by above 96%, as well as maintenance of low platelet numbers by repeated anti-CD42b administration every 48 h. Evaluation of MOG 35–55 -CD4 + accumulation at 14 dpi, showed significant reduction in blood, lymphoid organs and CNS tissues (Figure 1Bi–Biv) in the EAE-induced/platelet depleted group, relative to EAE-induced/isotype antibody-treated group. This group did not develop disease symptoms, as demonstrated by absence of clinical scores by experimental end point, whilst their isotype antibody-treated counterparts reached a mean clinical score of 2.25 ± 1.75 (Figure 1Ci).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine whether a direct relationship exists between platelet and MOG 35–55 -CD4 + accumulations, ICS was repeated in the presence of platelet depletion, which was induced from 7 dpi using an antibody against CD42b (or GP1bα). In our hands [25], this approach results in reduction in platelet numbers in all control and experimental groups by above 96%, as well as maintenance of low platelet numbers by repeated anti-CD42b administration every 48 h. Evaluation of MOG 35–55 -CD4 + accumulation at 14 dpi, showed significant reduction in blood, lymphoid organs and CNS tissues (Figure 1Bi–Biv) in the EAE-induced/platelet depleted group, relative to EAE-induced/isotype antibody-treated group. This group did not develop disease symptoms, as demonstrated by absence of clinical scores by experimental end point, whilst their isotype antibody-treated counterparts reached a mean clinical score of 2.25 ± 1.75 (Figure 1Ci).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study from our laboratory showed a cause and effect relationship between platelet accumulation and subsequent clinical disease development [25]. Here, we confirm this relationship with (1) evidence of a temporal relationship between platelet accumulation in the circulation and that of MOG 35–55 -CD4 + cells; (2) the demonstration of a dependence for MOG 35–55 -CD4 + cell accumulation in the blood, lymphoid organs as well as the CNS, on prior platelet accumulation; and (3) absence of immune cell infiltration and clinical EAE with platelet depletion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unequivocally demonstrating a crucial contribution of platelets to EAE disease pathogenesis, platelet depletion has attenuated EAE in mice, particularly in the effector phase of the disease; thereby, reducing CNS mRNA levels of CCL-2, CCL-5, CCL-19, CXCR-4, and IL-1β as well as the expression of adhesion molecule ICAM-1 ( 14 ) ( Figure 2 ). Consistently, recruitment of leukocytes to the inflamed CNS has been diminished by platelet depletion ( 14 , 160 ). Furthermore, administration of blocking antibodies against GPIIb/IIIa as well as platelet GPIb and its interaction with leukocyte counterreceptor Mac-1 has ameliorated EAE; thus, the involvement of platelets in EAE is regarded to be multi-faceted ( 14 ).…”
Section: Contribution Of Platelets To Neurovascular Inflammation In Nmentioning
confidence: 86%